This sporting life. - Storey, David (New York, Macmillan, 1960)
This Sporting Life is a 1960 novel by the English writer David Storey. It is set in Northern England and follows a man who tries to make it as a Rugby league player. It was the debut novel of Storey, himself a former player for Leeds.